KESEJAHTERAAN DALAM PERPEKTIF ISLAM: ANALISA EKONOMI KERAKYATAN - Fasya, Fasya (IAIN Langsa, 2016)
This article tends to perform a critical construction in building the welfare of populist economic. The economic analysis of society used a perspective that was created by Adi Sasono. According to Adi Sasono, the sustainability of populist economics of Indonesia today are often crushed by actopus capitalization. Therefore,this sustainability should be returned to the people according to sunnatullah, not only to restore to the populist economic, but also for social, and for society culture of Indonesia.